Jamaican first with ISO 14001 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The Jamaica Producers farms group comprising the island s Eastern and St Mary Banana Estates has been given ISO 14001 certification, the first agricultural entity in the Caribbean to do so. The ISO 14000 series of the International Standards...